h(x) = 4x - 10
Step-by-step explanation:
The given is:
f(x) = -2g(x) = 4x - 8We need to find h(x) = f(x) + g(x)
∵ f(x) = -2
∵ g(x) = 4x - 8
∵ h(x) = f(x) + g(x)
- Substitute f(x) and g(x) in h(x), and then add the like terms
∴ h(x) = (-2) + (4x - 8)
- Simplify the right hand side
∴ h(x) = -2 + 4x - 8
- Add like terms in the right hand side
∴ h(x) = 4x + (-2 - 8)
∵ -2 - 8 = -10
∴ h(x) = 4x + (-10)
∴ h(x) = 4x - 10
h(x) = 4x - 10
Learn more:
You can learn more about the functions in brainly.com/question/2645523
#LearnwithBrainly
Find m∠UVT m∠WVU = 169° m∠WVT = (2x + 20)° m∠UVT = (3x + 19)° A) 91° B) 94° C) 97° D) 100°\
Answer:
m ∠ UVT = 97° is the required answer.
Step-by-step explanation:
Given:
m∠WVU = 169°
m∠WVT = (2x + 20)°
m∠UVT = (3x + 19)°
To Find:
m∠UVT = ?
Solution:
Angle Addition Postulate is that if you place two angles side by side, then the measure of the resulting angle will be equal to the sum of the two original angle measures.
So By applying this property in the diagram below we get,
m∠ WVT + m∠UVT = m∠WVU ............{Angle Addition Postulate}
[tex](2x+20) + (3x+19) = 169\\5x + 39 = 169\\5x=169-39\\5x=130\\\therefore x=\frac{130}{5} \\\therefore x=26\\[/tex]
Now,
m∠UVT = (3x + 19)°
Substituting x = 26 we get
m∠UVT = 3 ×26 + 19
= 78 +19
∴ m∠UVT = 97°
Look at 4x + 5y - 12 - x + 3y . Have all of the like terms been combined? Explain in 1-2 sentences.
Answer:
no 4x and -x can be combined to form 3x, and 5y and 3y can be combned to form 8y. the correct equation should be 3x+8y-12
Step-by-step explanation:
Ten less than a number is three more than six times the number. Let n represent the number and translate each phase or sentence.
Required number is [tex]\frac{-13}{5}[/tex] and required expression is n – 10 = 6n + 3
Solution:Given that
Ten less than a number is three more than six times the number.
Number is represented by variable "n"
Need to determine equation and the number.
Ten less than number means subtracting 10 from the number
As number is n so ten less than number = n – 10 ------(1)
Six times the number = number multiplied by 6 = 6n
So three more than Six times the number = 6n + 3 --------(2)
As ten less than number is equal to 3 more than six times the number
=> n – 10 = 6n + 3
Solving the above expression for n we get
-10-3 = 6n – n
=> 5n = -13
[tex]\Rightarrow \mathrm{n}=-\frac{13}{5}[/tex]
Hence required number is [tex]-\frac{13}{5}[/tex] and required expression is n – 10 = 6n + 3
1. The half-life of the radioactive element krypton-91 is 10 seconds. If 32
grams of krypton - 91 are initially present, how many grams are present
after 30 seconds? Show the decay function. Use A = A0ekt
Answer:
4 g after 30 seconds.
Step-by-step explanation:
After 10 seconds 32 * 1/2 = 16 g are present.
After 20 seconds 32 * (1/2)^2 = 8 g are present
After 30 seconds 32 * (1/2)^3 = 4 g are present.
find the value of x in this figure
x equals 47 degrees
Explanation:Remember you must provide full questions in order to get excellent and precise answers. However, I have attached a figure in order to set the problem in context. Here we have a triangle. The most basic definition for a triangle is a polygon with three edges and three vertices, but there is something that is very important for all triangles:
The internal angles of every triangle add up to 180 degrees.By knowing this, we can write:
[tex]x^{\circ}+95^{\circ}+38^{\circ}=180^{\circ} \\ \\ Isolating \ x: \\ \\ x^{\circ}=180^{\circ}-95^{\circ}-38^{\circ} \\ \\ x^{\circ}=47^{\circ} \\ \\ \\ Where: \\ \\ \boxed{x=47}[/tex]
Learn more:Area of triangles: https://brainly.com/question/12051125
#LearnWithBrainly
What are the roots of the polynomial equation x cubed minus 5 x + 5 = 2 x squared minus 5?
To find the roots of the polynomial equation x^3 - 5x + 5 = 2x^2 - 5, rearrange the equation to equal zero and use methods such as synthetic division or factoring to solve the cubic equation.
Explanation:To find the roots of the polynomial equation x3 - 5x + 5 = 2x2 - 5, we need to set the equation equal to zero and rearrange it:
x3 - 2x2 - 5x + 5 + 5 = 0
x3 - 2x2 - 5x + 10 = 0
Now, we can use various methods to solve this cubic equation, such as synthetic division, factoring, or using a graphing calculator. On finding the roots of the equation, we can determine the values of x.
If f(x) = 1x1 + 9 and g(x) = -6, which describes the value of (f + g)(x)?
(f + g)(x) > 3 for all values of x
(f + g)(x) < 3 for all values of x
(f + g)(x) < 6 for all values of x
(f + g)(x) 6 for all values of x
Save and Exit
Ne
Mark this and return
Answer:
The answers are "(f+g)(x)> 3 for all values of x" and "(f+g)(x)<6 for all values of x".
Step-by-step explanation:
If f(x) = 1x1 + 9 =10, then f(x) is a constant for every value of x, which means that y=f(x) will take the value of 10 no matter which value takes x.If g(x)= -6, then g(x) is a constant for every value of x, which means that it will take the value of -6 no matter the value of x.(f+g)(x)=10 + (-6) = 10 - 6= 4. Then, no matter the value of x, the function (f+g)(x) will equal 4 (a constant). According to the available options, both "(f+g)(x)>3" and "(f+g)(x)<6" are true, because (f+g)(x)=4>3 and (f+g)(x)=4 <6.Claire Judice
Mixed Multistep Factoring (Equation)
Dec 01, 6:42:28 PM
Solve algebraically for all values of x:
5x5 + 6x4 + 80x3 + 96x² = 0
Answer:
Submit Answer
Answer:
The values of 'x' are -1.2, 0, 0, [tex]-4i[/tex] or [tex]4i[/tex].
Step-by-step explanation:
Given:
The equation to solve is given as:
[tex]5x^5+6x^4+80x^3+96x^2=0[/tex]
Factoring [tex]x^2[/tex] from all the terms, we get:
[tex]x^2(5x^3+6x^2+80x+96)=0[/tex]
Now, rearranging the terms, we get:
[tex]x^2(5x^3+80x+6x^2+96)=0[/tex]
Now, factoring [tex]5x[/tex] from the first two terms and 6 from the last two terms, we get:
[tex]x^2(5x(x^2+16)+6(x^2+16))=0\\x^2(x^2+16)(5x+6)=0[/tex]
Now, equating each factor to 0 and solving for 'x', we get:
[tex]x^2=0\\x=0\ and\ 0\\\\5x+6=0\\x=\frac{-6}{5}=1.2\\\\x^2+16=0\\x^2=-16\\x=\sqrt{-16}=\pm 4i[/tex]
There are 3 real values and 2 imaginary values. The value of 'x' as 0 is repeated twice.
Therefore, the values of 'x' are -1.2, 0, 0, [tex]-4i[/tex] or [tex]4i[/tex].
here is an equation that is true for all values of x:5(x+2)=5x+10. Elena saw this equation and says she can tell 20(x+2)=4(5x+10)+31 is also true for any value of x. How can she tell? Explain your reasoning.
Elena is wrong, because the two sides of equation are not equal for all values of x
Step-by-step explanation:
An equation of x is true for all values of x when the left hand side
is equal to the right hand side
To prove that an equation is true for all values of x do that
Simplify the left hand side and the right hand sideSolve the equation to find x, you will find the x in the left hand side is equal to x in the right hand side, so they canceled each other, and the numerical terms in the two sides equal each other, that means the equation is true for any values of xLets check that with given equation 5(x + 2) = 5x + 10
∵ 5(x + 2) = 5x + 10
- Simplify the left hand side
∵ 5(x) + 5(2) = 5x + 10
∴ 5x + 10 = 5x + 10
- Subtract 5x from both sides
∴ 10 = 10
∵ L.H.S = R.H.S
∴ The equation is true for all values of x
Lets do that with Elena's equation
∵ 20(x + 2) = 4(5x + 10) + 31
- Simplify the two sides of the equation
∵ 20(x) + 20(2) = 4(5x) + 4(10) + 31
∴ 20x + 40 = 20x + 40 + 31
- Add like terms in the right hand side
∴ 20x + 40 = 20x + 71
- Subtract 20x from both sides
∴ 40 = 71 ⇒ and that not true
∵ L.H.S ≠ R.H.S
∴ The equation is not true for all values of x
Elena is wrong, because the two sides of equation are not equal for all values of x
Learn more:
You can learn more about the equations in brainly.com/question/11306893
#LearnwithBrainly
Elena took the original equation, multiplied both sides of it by 4 and added 31 to both sides. Because she did the same thing to both sides of the equation, it is equal to the original equation and therefore is true for all values of `x`.
45pts help! what is the vertex of the function
f(x)=- -|x + 7| - 4
Answer: (-7, -4)
========================================
Explanation:
The general equation y = a| x-h | + k has the vertex (h,k)
Rewrite the original function in this form to get f(x) = -1|x - (-7)| + (-4) and we see that h = -7 and k = -4
So that's why the vertex is (h,k) = (-7, -4)
The V shape graph opens downward meaning that the vertex (-7, -4) is at the highest point. The graph is shown below. I used GeoGebra to make the graph.
Answer:
-7,-4
Step-by-step explanation:
AP:2,x,26.
Find the value of x
2,x, 26 are in A. P.
a2-a1 = a3-a2
x-2 = 26-x
2x = 26+2
2x = 28
So x = 14.
". As an operator in a chemical plant, you tenda
separating machine. After you fill the tank, the
content settles for 14 hours before the liquid is
removed. You fill the tank at 1:45 A.m. When do
you remove the liquid?
A.
2:15 A.M.
B. 2:45 A.M.
C. 3:00 A.M.
D. 3:15 A.M.
E. 3:45 A.M.
Answer:
3:45 P.M.
Step-by-step explanation:
After I fill the tank, the content settles for 14 hours before the liquid is removed.
So, the liquid is removed after content settlement i.e. after 14 hours of filling up the tank.
If I fill the tank at 1:45 A.M. then after 14 hours i.e. at 3: 45 P.M I will remove the liquid.
If we separate the 14 hours into (12 hours + 2 hours), then by adding 12 hours the time will remain the same, only the A.M. will change to P.M i.e. 1: 45 P.M. and then by adding 2 hours more the time will be 3:45 P.M. (Answer)
Kristina used synthetic division to divide the polynomial f(x) by x−2, as shown on the table. What is the value of f(2)? −14 −11 −2 −1 A synthetic division setup with respective columns containing the following numbers column 1 containing two as a divisor, column 2 containing negative 1, blank and negative 1, column 3 containing negative 5, negative 2, negative 7, and column 4 containing three, negative 14, negative 11.There is a line above the numbers negative 1, negative 7 and negative 11.
Answer:
-11
Step-by-step explanation:
The answer to the first one sould be -11
2x^3 +5x^2−x−6
Write 5x^2 as 4x^2 + x^2......and we have.....
2x^3 + 4x^2 + x^2 - x - 6
2x^2 ( x + 2) + ( x + 2)(x - 3)
(x + 2) [ 2x^2 + x - 3]
(x + 2) (2x +3) (x - 1)
x^3−4x^2−3x+18 = 0
Using some synthetic division, we have
3 [ 1 - 4 -3 18 ]
3 -3 -18
_______________
1 -1 -6 0
The remaining polynomial is x^2 - x - 6 which factors as (x - 3) ( x + 2)
So .... the factored form is (x - 3) ( x - 3) ( x + 2) = ( x + 2) ( x - 3)^2 = 0
Answer:
-11 is correct for all future users.
Step-by-step explanation:
Evaluate the expression. ab if a = 6 and b = 7
Answer:
42
Step-by-step explanation:
ab is a x b
[tex]a \times b[/tex]
[tex]6 \times 7 = 42[/tex]
Answer:279,936
Step-by-step explanation:
i hope its helps
Find the slope of the line that goes through the given points.
(3, 5) and (3, -5)
For this case we have that by definition, the slope of a line
is given by:
[tex]m = \frac {y_ {2} -y_{1}} {x_ {2} -x_ {1}}[/tex]
Where:
[tex](x_ {1}, y_ {1})\ and\ (x_ {2}, y_ {2})[/tex] are two points through which the line passes.
According to the statement we have:
[tex](x_ {1}, y_ {1}): (3,5)\\(x_ {2}, y_ {2}): (3, -5)[/tex]
Substituting we have:
[tex]m = \frac {-5-5} {3-3}[/tex]
It is noted that the slope is undefined.
Answer:
The slope is undefined
The function relating the height of an object off the ground to the time spent falling is a quadratic relationship. Travis drops a
tennis ball from the top of an office building 90 meters tall. Three seconds later, the ball lands on the ground. After 2
seconds, how far is the ball off the ground?
Answer:
the ball is on the ground after 3 seconds right so it would still be on the ground
Step-by-step explanation:
Answer:50 meters
Step-by-step explanation:
Given: ΔАВС, m∠ACB = 90°
CD
⊥
AB
, m∠ACD = 60°,BC = 6 cm
Find CD, Area of ΔABC
Answer:
CD = 5.196 cm
Area = 31.177 sq. cm.
Step-by-step explanation:
See the attached diagram.
Given that ∠ ACB = 90° in Δ ABC.
Now, CD ⊥ AB and ∠ CDB = ∠ CDA = 90°
Given that ∠ ACD = 60° and BC = 6 cm.
We have to find the length of CD and the area of Δ ABC.
Now, ∠ CAD = 90° - ∠ ACD = 90° - 60° = 30°
Again, ∠ CBD = 90° - ∠ CAD = 90° - 30° = 60°.
Now, from Δ BCD, [tex]\sin 60 = \frac{CD}{BC} = \frac{CD}{6}[/tex]
{Since Δ BCD is a right triangle and ∠ CDB = 90°}
⇒ [tex]CD = 6 \times \sin 60 = 5.196[/tex] cm. (Answer)
Now, from Δ ACD, [tex]\sin 30 = \frac{CD}{AC} = \frac{5.169}{AC}[/tex]
{Since Δ ACD is a right triangle and ∠ ADC = 90°}
⇒ [tex]AC = \frac{5.196}{\sin 30} = 10.392[/tex] cm
So, the area of Δ ABC = [tex]\frac{1}{2} \times BC \times AC = \frac{10.392 \times 6}{2} = 31.177[/tex] sq. cm. (Answer)
Answer:
CD=3√3
Step-by-step explanation:
Anyone, please help. I’m a dimwit at math!
Answer: it should be "B. 73" if I'm incorrect sorry but it should be "B. 73"
Step-by-step explanation:
Find the slope of :
1. (−1, 3) and (5, 4.5)
2. (8.1, −2) and (5.3, −2)
Answer:
General formula of slope=change in y/change in x
1:0.25
2:0
the area of a rectangle is 90 in2^. the ratio of the length to the width is 5:2. find the length and the width
Length and width of rectangle is 15 inches and 6 inches respectively
Solution:Given that area of a rectangle is 90 square inch
Ratio of length to the width = 5: 2.
Need to determine length and width of rectangle.
As ratio of length to the width is 5 : 2
Lets assume length of rectangle = 5x inches and width of rectangle = 2x inches.
The formula for area of rectangle is given as:
[tex]\text { Area of rectangle }=\text { length of rectangle } \times \text { width of rectangle}[/tex]
Substituting the given value of area of rectangle and assumed value of length and width of rectangle we get:
[tex]\begin{array}{l}{90=5 x \times 2 x} \\\\ {=>90=10 x^{2}}\end{array}[/tex]
On solving the above expression for x we get
[tex]\begin{array}{l}{=>\frac{90}{10}=x^{2}} \\\\ {=>x^{2}=9} \\\\ {=>x=\sqrt{9}=3}\end{array}[/tex]
[tex]\begin{array}{l}{\text { Length of rectangle }=5 \times x=5 \times 3=15 \text { inches }} \\\\ {\text { Width of rectangle }=2 \times} x=2 \times} 3=6 \text { inches }}\end{array}[/tex]
Hence length and width of rectangle is 15 inches and 6 inches.
How much grams of cheese do Olivia and sara have together
Answer:
they have 214 grams of cheese together
Answer:
214g
Step-by-step explanation:
Sara has 84 grams of cheese.
Olivia has 130 grams of cheese.
Total amount of cheese = Sara's cheese + Olivia's cheese
Total amount of cheese = 84 + 130
214 = 84 + 130
Use the information given to identify the a7 term of the geometric sequence: a2 = −5, r = 2
Answer:
[tex]a_{7}[/tex] = - 160
Step-by-step explanation:
The n th term of a geometric sequence is calculated as
[tex]a_{n}[/tex] = a₁[tex](r)^{n-1}[/tex]
where a₁ is the first term and r the common ratio
Given
a₂ = - 5, then
a₁r = - 5, that is
2a₁ = - 5 ⇒ a₁ = - 2.5, thus
[tex]a_{7}[/tex] = - 2.5 × [tex](2)^{6}[/tex] = - 2.5 × 64 = - 160
Is 12/30 and 18/45 proportional, or not proportional?
12/30 = 18/45, so first you're going to cross multiply and you'll get (30)(18) = (12)(45). Then you can see that 540 = 540 same number so they're proportional...
BTW THIS WAY IS A LOT EASIER.
12/30 = 2/5
18/45 = 2/5
So yes, in summary, they're proportional to each other. Hope this helps, have a BLESSED and wonderful day! :-)
Answer:
proportional
Step-by-step explanation:
12/30 multiplied by a factor of 1.5 is 18/45 so it is proportional
What’s the answer for 1/2x-9=-25
Answer:
-32
Step-by-step explanation:
1/2x-9=-25
1/2x= -25+9
1/2x=-16 /multiply 2
x=-32
[tex]\text{Hello there!}\\\\\text{Solve:}\\\\\frac{1}{2}x-9=-25\\\\\text{Add 9 to both sides}\\\\\frac{1}{2}x=-16\\\\\text{Divide both sides by 1/2 or 0.5}\\\\\boxed{x=-32}[/tex]
In the given triangle, ∠AED ∼ ∠ ABC, AD = 6.9, AE = 7.2, DE = 5.2, and BC = 10.2. Find the measure of BD and CE. Round your answer to the nearest tenth.
Answer:
The measure of side BD is 8.6 and The measure of side CE is 8.4
Step-by-step explanation:
Given as :
The Triangle is ABC with side AB , BC , CA
And The points E and D is on the side AB and AC
So, AED is a Triangle
And Δ AED [tex]\sim[/tex] Δ ABC
The measure of side AD = 6.9
The measure of side AE = 7.2
The measure of side ED = 5.2
The measure of side BC = 10.2
Let The The measure of side EB = x
And The measure of side DC = y
So, From similarity property
[tex]\dfrac{AB}{AE}[/tex] = [tex]\dfrac{AC}{AD}[/tex] = [tex]\dfrac{BC}{ED}[/tex]
Or, [tex]\dfrac{AB}{AE}[/tex] = [tex]\dfrac{BC}{ED}[/tex]
So, [tex]\dfrac{7.2 + x}{7.2}[/tex] = [tex]\dfrac{10.2}{5.2}[/tex]
Or, 5.2 × ( 7.2 + x ) = 10.2 × 7.2
Or, 37.44 + 5.2 x = 73.44
Or, 73.44 - 37.44 = 5.2 x
∴ x = [tex]\frac{36}{5.2}[/tex]
I.e x = 6.9
Now in Δ BED
BE² + ED² = BD²
Or, 6.9² + 5.2² = BD²
Or, BD² = 74.65
∴ BD = [tex]\sqrt{74.65}[/tex]
I.e BD = 8.64
Or, BD = 8.6
Similarly for y
[tex]\dfrac{AC}{AD}[/tex] = [tex]\dfrac{BC}{ED}[/tex]
Or, [tex]\dfrac{6.9+y}{6.9}[/tex] = [tex]\dfrac{10.2}{5.2}[/tex]
Or, 5.2 × ( 6.9 + y ) = 10.2 × 6.9
Or, 35.88 + 5.2 y = 70.38
or, 5.2 y = 70.8 - 35.88
Or, 5.2 y = 34.5
∴ y = [tex]\frac{34.5}{5.2}[/tex]
I.e y = 6.6
Now in Δ CED
CD² + ED² = CE²
Or, 6.6² + 5.2² = CE²
Or, CE² = 70.6
∴ CE = [tex]\sqrt{70.6}[/tex]
I.e CE = 8.40
Or, CE = 8.4
Hence The measure of side BD is 8.6 and The measure of side CE is 8.4 Answer
Answer:
By using geometric calculations,the measure of BD and CE are 6.9 and 7.4 respectively.
3x minus 7 divided by 2 equals negative 5
Answer: x=0.5
Step-by-step explanation: In order to solve this problem, you need to simplify the rest of the problem first. You can do this by dividing -7 by 2, which will result in -3.5, making the equation 3x-3.5=-5. If you add 3.5 to both sides, the equation becomes 3x = 1.5. If you divide 1.5 by 3, you are left with 0.5, so x=0.5.
Final answer:
The solution to the linear equation '3x minus 7 divided by 2 equals negative 5' is found by performing algebraic operations to isolate the variable, resulting in x = -1.
Explanation:
The question involves solving a linear equation which is a fundamental concept in mathematics. To solve the equation 3x minus 7 divided by 2 equals negative 5, you will perform algebraic operations to isolate the variable x. Here is a step-by-step process:
Multiply both sides of the equation by 2 to get rid of the denominator: 2 * (3x - 7)/2 = -5 * 2.Simplify both sides: 3x - 7 = -10.Add 7 to both sides to isolate the 3x term: 3x = -10 + 7.Simplify the right side: 3x = -3.Divide both sides by 3 to solve for x: x = -3/3.Finally, x simplifies to -1 as the solution.Applying this process, you can see that the original equation is satisfied when x = -1, which completes our solution.
Okay, how many weeks would you have to work to pay for Gary's $1200 mistake?
The number of weeks requires is 15 weeks
What is Unitary method?It is a method where we find the value of a single unit from the value of multiple units and the value of multiple units from the value of a single unit.
Steps to Use Unitary Method
First, let us make a note of the information we have. There are 5 ice-creams. 5 ice-creams cost $125.
Step 1: Let’s find the cost of 1 ice cream. In order to do that, divide the total cost of ice-creams by the total number of ice-creams. The cost of 1 ice-cream = Total cost of ice-creams/Total number of ice-creams = 125/5 = 25. Therefore, the cost of 1 ice cream is $25.
Step 2: To find the cost of 3 ice-creams, multiply the cost of 1 ice cream by the number of ice-creams. The cost of 3 ice-creams is cost of 1 ice-cream × number of ice-creams = 25 × 3 = $75. Finally, we have the cost of 3 ice-creams i.e. $75.
Given:
$85.00 a week just from Allowance
So, Gary have to work
=1200/85
= 15 weeks
Hence, the number of weeks requires is 15 weeks.
Learn more about unitary method here:
https://brainly.com/question/22056199
#SPJ2
The complete question is
can someone help me please?
Question : If you have a job or allowance, how much do you take home per week?
I put that I make $85.00 a week just from Allowance and my half job.
So the question is : how many weeks would you have to work to pay for Gary's $1200 mistake?
[calculate $1200 � your take home pay amount = answer in weeks]
Weeks for Laptop:
how many weeks would you have to work to pay for your little mistake with the $13 bounced check? You know, that $4300 messup? Weeks for pizza :
Help please thanks
Final answer:
Jason will have to work approximately 6.67 weeks, or about 6 weeks and 5 days, to pay off a $1200 mistake if he earns $4.50 per hour after government income reduction.
Explanation:
To calculate how many weeks a student would have to work to pay for a $1200 mistake, we will use the information provided about Jason's income and work scenario as a reference. According to the information, Jason nets $4.50 for every hour of work due to a reduction in government income. Thus, if Jason has to repay $1200, we will divide this amount by his net hourly income to find the total hours he needs to work.
$1200 ÷ $4.50 per hour = 266.67 hours
Now, to convert these hours into weeks, we assume a standard work week is 40 hours. Therefore, we divide the total hours by 40 hours per week.
266.67 hours ÷ 40 hours per week = 6.67 weeks
Jason will have to work approximately 6.67 weeks to pay off a $1200 mistake.
What is a mineral?
a. an element
b. a rock formed from something that was once living
c. a naturally formed solid substance with a crystal structure
Answer:
The answer is definitely C. a naturally formed solid substance with a crystal structure
Are the expressions 4b-7-
2b + 11 and b + 3+ b + 1
equivalent?
Answer:
2b+4 so yes there are equivalent
Step-by-step explanation:
4b-7-2b+11
4b-2b-7+11
2b+4
b+3+b+1
2b+4
help help help help
Answer:
The correct answer is Helena